Sustaining the High-Level TVET Education Programme - Azizul Helmi, Sofian (UMPSA, 2023)
PAKA, 18 July 2023 - The perception of Technical and Vocational Education and Training (TVET) programmes as secondary class options must be stopped to ensure the sustainability of TVET programmes offered in the country, especially the high-level TVET programmes that remain the top choice for students after completing their secondary education.